: Se essa cidade fosse minha: Uma cartilha informativa sobre o planejamento da cidade - Ferreira, Larissa Bernardo (2024)
Living in and accessing the city takes on different views against the scenarios shaped by urban management and planning. Despite affecting the daily lives of the entire population, the access to related discussions is embedded in practices that do not encourage citizen participation - whether through pseudo-participatory procedures or the technical language used when technic and popular perspectives meet. For this reason, this work seeks to clarify general topics discussed in the professional and academic field about city development and its planning through an illustrated explanatory booklet, given the relevance of urban education in this context. To this end, an effort was made to understand the importance of popular participation in these processes, which is strongly reinforced by the Estatuto da Cidade (Law 10.257/2001). It was also important to investigate the popular perception of the city problematics through the Community Diagnostic document produced during the process of revision of the João Pessoa - PB’s Master Plan and from there, seek to work on the selected themes for this first volume. In this light, the relevance of citizen inclusion in the process of urban planning and related discussions is reinforced as a civil right and a fundamental effort to build fairer and sustainable cities, where urban planning and management work toward the actual needs of its citizens.